Late Quaternary changes in paleoproductivity and hydrographyin the Azores region deduced from coccolithophore assemblages - Schwab, Christian (2013)
Marine sediment cores provide the opportunity to study past climatic changes, which is essential to understand the ongoing and future climate change. Within this context, the North Atlantic Ocean is one of the best-studied areas. However, most of these studies focus on the continental margins and shelfs, where thick piles of sediment allow a detailed reconstruction of past environmental changes. In contrast, little is known about the low- to midlatitude open ocean areas, which would be crucial regarding the large area covered. Furthermore, the low latitudes of the North Atlantic are considered to play a key role in modulating the global climate on at least orbital and millennial timescales. This key role is attributed to their ability to retain/release heat to the higher latitudes and therefore to influence the Atlantic Meridional Overturning Circulation (AMOC). Especially changes in marine primary productivity, which due to their impact on the ocean carbon cycle are an integral part of the climate system, are of interest to the (paleo-) climate community. Therefore, in this PhD thesis, changes in primary productivity and hy-drography were reconstructed with high temporal resolution in the temperate/subtropical open ocean North Atlantic, from three sediment cores (GEOFAR KF16, MD08-3179Cq and MD08-3180Cq) taken slightly south of the Azores Islands. These reconstructions are primarily based on quantitative analysis of coccolithophore assemblages, which are supplemented by alkenone analysis, X-ray fluorescence (XRF) core scanning and diatom counts. The results indicate that profound changes in productivity and in hydrographic conditions occurred during the selected time periods of the last 130 kyrs in the Azores region, which can convincingly be deduced from changes in coccolithophore assemblages. For example, an increased productivity prevailed in the Azores region during the last deglacial and early Holocene, especially during cold Heinrich event 1 (H1) and the cold Younger Dryas that are characterized by a ...